O papel do professor na formação docente indígena: uma reflexão a partir das impressões dos professores formadores que atuaram no curso de licenciatura para professores indígenas do Alto Solimões - Nascimento Filho, Virgílio Bandeira do (2014)
The goal of this study is to report on the impressions of the professors who worked in the teaching program for indigenous teachers of the Alto Solimões implanted by the University of the State of Amazonas in the Torü Nguepataü Training Center of the Ticunas Teachers in the Fildelélfia/Benjaming Constant/AM community. It was based on bibliographic analysis and in loco observations so as to comprehend the indigenous university as an organizational space. It also is based on the application of questionnaires to the educators who worked on the modules during the development of the program. The subjects who participated in the research were ten professors of the regular faculty of the Center for Higher Studies of Tabatinga/UEA. These were chosen as a result of the experience they had in regular higher learning programs as there were quotas for indigenous people in that institution. Within the results it was observed that the UEA structured a framework for the development of the activities carried out in Filadélfia which provided food, water and a structure of dormitories in Fildadélfia to give support to the different ethnic groups which made up the group of students. The activities of the program were carried out in modules, being completed in 5 years, divided into two periods per year. In their reports the teachers listed that the main difficulties which interfere with teaching and learning were the immediate non acceptance of the implantation of a higher learning program in their community, not understanding the Portuguese language, timid posture, low intonation of the voice and vocabulary of the texts distant from the indigenous reality. However, it is up to the professor to re-signify the contents in the constitution of knowledge facilitating the learning process of the students, becoming researchers of their own culture. With this attitude those educators were able to participate in the training of two hundred and four indigenous people in the teaching programs in Anthropology, Art, Biology, Physical Education, Languages and Mathematics, marking a beginning in the process of transformation of the education framework in the region of Alto Solimões.